Always looking up : the adventures of an incurable optimist - Fox, Michael J., 1961- (New York : Hyperion, 2009)
Michael J. Fox shares his personal outlook on maintaining the positive attitude that has lifted him through the difficult times. Fox shows us how to live a more appreciative and fulfilling life by recognizing the things we already have
Keywords: Fox, Michael J., -- 1961-; Actors -- Canada -- Biography; Actors -- United States -- Biography